The Internalization of Religious Moderation Values Towards The Youth Through Qurany Song in Jombang - Mustofa, Ali; Indana, Nurul (Proceedings of Annual Conference for Muslim Scholars, 2023)
This study was about internalization of religious moderation values to Jombang youth and Sufism poetry (Qur'any songs), the research was aimed to analyze the process of religious moderation internalization values to the youth through Sufism poetry (Qur'any songs). This research used qualitative case study. Data was collected through interviews, observation and documentation, the data then was analyzed using data display, condensation, and drawing conclusions. To test the validity of data, the researcher used sources and techniques triangulation. The result showed that the internalization of the religious moderation values was done through three stages, such as: transformation value was done through teaching poetry (Qur'anic songs) by holding regular recitations. The transaction value was done through explaining the meaning of the poetry content and the Trans internalization was conducted through practicing amaliyah of the poetry. The moderate values appeared were tawassuth, tasammuh, i'tidal, tawazzun and shidiq